Productive performance of piglets fed with different sources of lactose - Jimmy Quisirumbay-Gaibor; Luis Delgado, César Oña; Alexandra Naranjo; Eduardo Aragón (African Journal of Pig Farming, 2017)
Lactose is important to potentiate the health and growth of piglets before and after weaning. The aim of this study was to evaluate the effect of three sources of lactose on performance: 24 piglets from 7 days of age were divided into three groups (n = 8), 2 dietary phases were used: pre-weaning (7-35 days) and weaning (36-56 days). The source of lactose was the variable under study: Crystallized lactose, lacto-whey and permeate. Body weight (BW), Average Daily Gain (ADG) and Feed Conversion Rate (FCR) were the parameters evaluated. The results were analyzed by ANADEVA and DUNCAN. Piglets receiving the permeate had a higher final weight 23.98 kg (P> 0.05) and higher ADG 0.42 kg / d (P> 0.05). This experiment determined that any source of lactose can be included in feed processing for piglets however the inclusion of permeate cheaper production costs.